The effectiveness of loyalty program towards customer loyalty / Mohammad Zaim Mohd Salleh ...[et al.] - Mohd Salleh, Mohammad Zaim; Muhamad Yunus, Nor Sara Nadia; Abdul Ghani, Nadiah Maisarah; Arifin, Norafifa; Mohd Ali, Ainunnazlee (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, 2018)
In the business field it is very important to win the customer heart and the success of the loyalty program offered to the customers depends on particular rewards given by the service provider. Loyalty and customer loyalty in previous research has shown a significant relationship. There are problems occurs in loyalty program where the customers has a low awareness about the loyalty program, and the delayed in receiving the rewards. Loyalty program are divided into two parts. The first part is soft attribute loyalty program and second part is hard attribute loyalty program. Soft attributes loyalty program are ways of doing things or code of conduct that are intangible and was meant to give customer sense of recognition. Hard attributes loyalty program are basically tangible elements such as discounts card and free gift. A total of 100 respondents were chosen from one selected retailers in Penang and a purposive sampling technique was used. The result shown that both hard and soft attribute has a significant relationship with customer loyalty.